2016
DOI: 10.1134/s0006297916110158
|View full text |Cite
|
Sign up to set email alerts
|

Study of immunomodulatory effects of extracellular HSP70 in a mouse model of allergic airway inflammation

Abstract: Immunostimulatory properties of extracellular heat shock proteins 70 kDa (HSP70) became interesting for investigators a long time ago. However, in recent years a series of works showing a significant relation of the immunostimulating effects of recombinant HSP70 to contamination of the protein samples with bacterial endotoxins (lipopolysaccharide, LPS) has been published. The authors showed that intensive elimination of LPS from the protein samples resulted in inversion of immunostimulating effects of HSP70 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…For example, mycobacterial Hsp60 and Hsp70 were shown to induce anti-inflammatory factors such as IL-10 expression by T cells [ 67 , 102 ]. It is thus not surprising that some heat shock proteins have entered the clinical trials pipe-line against conditions such as rheumatoid arthritis and autoimmune type I diabetes [ 122 , 123 ]. There is no question that the focus on heat shock proteins as immune modulators towards clinical interventions will continue to grow.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mycobacterial Hsp60 and Hsp70 were shown to induce anti-inflammatory factors such as IL-10 expression by T cells [ 67 , 102 ]. It is thus not surprising that some heat shock proteins have entered the clinical trials pipe-line against conditions such as rheumatoid arthritis and autoimmune type I diabetes [ 122 , 123 ]. There is no question that the focus on heat shock proteins as immune modulators towards clinical interventions will continue to grow.…”
Section: Discussionmentioning
confidence: 99%
“…The data from our study indicate that Hsp70 positively regulates airway inflammation and Th2 immune responses in SEA-induced allergic airway inflammation. However, other studies have reported that Hsp70 acts as a negative modulator, including in asthma (24,38). Shevchenko et al (24) addressed the modulatory effect of extracellular Hsp70 using ovalbumin-induced allergic inflammation of the airways in mouse and showed that an exogenous and autologous oropharyngeal administration of Hsp70 in ovalbuminchallenged mice was sufficient to decrease BAL fluid type 2 cytokine secretion and inflammatory cell infiltration.…”
Section: Hsp70 Induces Th2 Responses and Airway Inflammationmentioning
confidence: 98%
“…Furthermore, asthmatic patients have elevated levels of Hsp70 in induced sputum and serum compared with healthy subjects, and this increase correlates with disease severity (23). Those studies have suggested a proinflammatory role for Hsp70 in the development of allergic diseases, whereas other reports have described Hsp70 as an anti-inflammatory mediator (24). The role of Hsp70 in allergic diseases has been associated with divergent or dual conclusions, ranging from pro-to anti-inflammatory effects.…”
mentioning
confidence: 99%
“…In our studies, we observed that elevated Itg β1 did not change the levels of HSP70, a family of molecular chaperones that protect cells from stress, regulate cell adhesion and invasion through the modulation of integrins β1, β2, and β3 and integrin-associated signaling molecules [ 111 ]. HSP70 is also known to prevent or arrest inflammation, and HSPs, in general, have been shown to promote the production of anti-inflammatory cytokines [ 112 ].…”
Section: Discussionmentioning
confidence: 99%